Autoimmune disease and oral squamous cell carcinoma: A systematic review. (12th July 2021) - Pillai, Anjali; Adilbay, Dauren; Matsoukas, Konstantina; Ganly, Ian; Patel, Snehal G.
Abstract: Background: Oral cancer is typically related to environmental carcinogen exposure including tobacco and alcohol. Other less investigated risk factors may be related to a suppressed or dysregulated immune state, and in oral cancer, various levels of immune dysregulation have been found to affect survival and recurrence rates. The rationale for this systematic review was to investigate the possible role that a growing chronic host condition like an autoimmune disease may play in this disease. Methods: A systematic search of the literature was carried out using four electronic databases in order to identify original research of any analytic study design type that investigated the relationship between autoimmune disease and oral cancer. Out of 1, 947 identified records, 24 observational studies were included for qualitative synthesis. Results: The studies varied in end points ranging from overall survival (OS), standardized incidence ratio (SIR), and hazard ratio (HR). Due to the heterogenous sampling of studies even within the same study design group, a meta‐analysis was not employed. The current state of the literature is varied and heterogenous in both study design and endpoints. Conclusion: Major limitations existed introducing significant bias especially in determining cancer risk such as lack of information surrounding known etiologic risk factors such as alcohol and tobacco consumption. Despite these limitations, a signal was seen between autoimmune disease and oral cancer outcomes and risk. Future studies investigating the relationship between autoimmune disease and oral cancer in a more focused and quantitative manner are therefore needed.